Social studies teachers' perspectives on water literacy - Öner, Ümmühan; Toprak, Yakup (Tokat Gaziosmanpaşa Üniversitesi, 2026)
Water is considered the fundamental source of life and is among the most important issues requiring collective effort from all segments of society for its protection. Water resources are under significant threat due to factors such as the continuously growing human population, air pollution, and unconscious consumption of resources. This situation highlights the importance of the concept of water literacy regarding water, which is recognized as the most indispensable source of life in a changing and developing world. Teachers bear the most important responsibility in fostering this concept. The purpose of this study is to determine social studies teachers' views on water literacy. The research was conducted using a "phenomenological" design. The study group consists of 20 social studies teachers working in Diyarbakır during the spring semester of the 2022-2023 academic year. The study group was formed using "convenience sampling," one of the purposive sampling methods. A semi-structured interview form developed by the researchers was used as the data collection tool. The data were analyzed using content analysis. The study concluded that there is a relationship between social studies and water literacy, that the lecture method is predominantly used for water-related topics in social studies classes, and that water literacy can be effectively taught through collaboration with science courses. Additionally, it is recommended to use student-centered methods and techniques in developing water literacy, to include relevant learning outcomes in the social studies curriculum, to establish collaboration between social studies and other courses, and to develop a comprehensive water literacy program that progresses in a spiral manner from elementary school through university.
Keywords: Social Studies Education; Sosyal Bilgiler Eğitimi